2017
DOI: 10.5902/2179460x23281
|View full text |Cite
|
Sign up to set email alerts
|

Atividade Citotóxica Do Extrato De Croton Urucurana Baill Contra Linhagens De Células Leucêmicas Humanas U937 E Thp1

Abstract: RESUMO As leucemias são neoplasias malignas que acometem as células do sangue e têm origem na medula óssea. São cânceres de grande incidência e de difícil tratamento, havendo, portanto, a uma constante procura por terapias

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…Other researchers have shown a dose-dependent effect over time, as proposed by Vieira et al [10], which demonstrated apoptosis in cell line U937 and THP-1 by the extract of Croton urucurana in a single application dose. They showed that at concentrations of 400 and 800 µg/mL, and over a period of 48 hours, the extract promotes 75% of apoptosis, demonstrating the desired effect, over a long period, from the ethanol extract.…”
Section: Discussionmentioning
confidence: 79%
“…Other researchers have shown a dose-dependent effect over time, as proposed by Vieira et al [10], which demonstrated apoptosis in cell line U937 and THP-1 by the extract of Croton urucurana in a single application dose. They showed that at concentrations of 400 and 800 µg/mL, and over a period of 48 hours, the extract promotes 75% of apoptosis, demonstrating the desired effect, over a long period, from the ethanol extract.…”
Section: Discussionmentioning
confidence: 79%
“…Outros estudos envolveram a investigação de propriedades antibacterianas e antioxidantes do óleo essencial das folhas (SIMIONATTO et al, 2007) e atividade citotóxica do extrato da casca contra linhagens de células leucêmicas humanas (VIEIRA et al,2017).…”
Section: Introductionunclassified
“…Popularly known as sangra d´água, it is used as antiinflammatory, anti-hemorrhagic, healing, in the fight against prostate cancer, diabetes and kidney disease (ANTONIAZZI et al, 2016). Some studies report the chemical composition and biological actions for latex, essential oil and different parts of the plant, highlighting cytotoxic, antimicrobial and antinociceptive activities (CANDIDO-BACANI et al, 2015;SIMIONATTO et al, 2007;SIMIONATTO et al, 2009;VIEIRA et al, 2017;CORDEIRO et al, 2016).…”
Section: Introductionmentioning
confidence: 99%